ANALISIS POLA PERSEBARAN COUNTER HANDPHONE DAN VOUCHER ISI ULANG DI KOTAYOGYAKARTA (Studi Kasus Persebaran Distribusi Counter AXIS Tahun 2010) - , DWI ISTANTO; , Abdur Rofi, S.Si, M.Si., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Yogyakarta known as the city of education and cultural, this city is one of the tourism destinations in Indonesia which has evolved from various sectors of the economy especially sector trade. That is developing counter handphone and pre-paid voucher. By year to year the business has been moving up significantly, due to the need of communication via mobile phones has changed, from the tertiary to the primary needs. The purpose of this research is to know the characteristics counter, encircle the development pattern how counter handphones and pre-paid voucher. Research method is used methods or observation, logging and measurement in the field, making border areas pengcoveran and doing interviews with those who are considered to be aware of the existence counter in Yogyakarta with the method data analysis descriptive statistics. When viewed from the place of business ownership status, they prefer to rent a place (62%) to built their counter. While according to business areas, housing area are very interested for the successful business counter handphone and pre-paid voucher in Yogyakarta (30.2%), with the kinds of business places is a kiosk (91.7%). For the location is divided into six counter type, from the six types of location was chosen location hook ( corner) (38%), while for size counter was built with size < 5 mÂ² (67.4%). In the election type way, 48.9% choose location along the way page or protocol. Counter handphones and pre-paid voucher in Yogyakarta is not only are concentrated in one place, but spread in all sub-districts that there is in Yogyakarta . Encircle counter handphone and pre-paid voucher generally found in along the network urban Yogyakarta. In the network with accessibility that was generally there are many shops and office buildings or other centers such as hospitals, hotels lodging, campus. From the result of the research can be concluded that the distribution counter handphone and pre-paid voucher more standing in the region, with high accessibility , and also the region, with its population density facilities services .